Parenthood decisions in uncertain times: Experimental evidence from four countries - Arnstein Aassve; Letizia Mencarini; Chen Peng; Samuel Plach; Alonso Román Amarales; Maria Letizia Tanturri (Proceedings of the National Academy of Sciences, 2026)
Fertility rates are declining across much of the globe, yet the forces driving this decline have become increasingly complex, and classic theories have become less adequate to explain recent trends. While economic and gender-related explanations have long dominated fertility research, emerging global uncertainties, such as climate change, democratic backsliding, economic crises, and regional conflicts, may also shape how individuals evaluate childbearing. In addition to the more classical factors, this cross-national study examines how macrolevel uncertainties influence perceptions of fertility intentions in Italy, Argentina, the United States, and Germany. These countries offer distinct fertility trajectories and face unique combinations of sociopolitical and environmental challenges. Using a conjoint experiment, we examine how individuals evaluate, across hypothetical scenarios, their intention of having a child under varying household, policy, and macrolevel conditions. Across all four countries, material security remains central: household income is the strongest predictor of fertility intentions, with homeownership and childcare playing smaller roles. At the same time, perceptions of macrolevel stability, including expectations about climate conditions, economic prospects, democratic functioning, and peace, exert substantial and meaningful effects, comparable to homeownership and childcare provision but more pronounced than those associated with gender-role arrangements. Cross-country differences show that macroeconomic stability and climate change are most consequential in Argentina, while in the United States respondents are less responsive to geopolitical conflict. These findings show that individuals evaluate childbearing not only through their immediate circumstances, but also through expectations about broader societal futures, highlighting the importance of incorporating macrolevel uncertainty when explaining contemporary fertility decline.